2019
DOI: 10.1002/pro.3734
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic relaxation enhancement‐assisted structural characterization of a partially disordered conformation of ubiquitin

Abstract: Nuclear magnetic resonance (NMR) is a powerful tool to study three‐dimensional structures as well as protein conformational fluctuations in solution, but it is compromised by increases in peak widths and missing signals. We previously reported that ubiquitin has two folded conformations, N1 and N2 and plus another folded conformation, I, in which some amide group signals of residues 33–41 almost disappeared above 3 kbar at pH 4.5 and 273 K. Thus, well‐converged structural models could not be obtained for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Information regarding localized conformational dynamics and thermodynamic stability might be useful for the rational design of effective OspA vaccines. Moreover, since PRE observation under high‐pressure is only limited in ubiquitin, 27 the present is a confirmation of PRE under high‐pressure. A combination of PRE‐assisted high‐pressure NMR and MD simulation is, in general, useful for characterizing the dynamic structures of functionally essential protein intermediates.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Information regarding localized conformational dynamics and thermodynamic stability might be useful for the rational design of effective OspA vaccines. Moreover, since PRE observation under high‐pressure is only limited in ubiquitin, 27 the present is a confirmation of PRE under high‐pressure. A combination of PRE‐assisted high‐pressure NMR and MD simulation is, in general, useful for characterizing the dynamic structures of functionally essential protein intermediates.…”
Section: Resultssupporting
confidence: 61%
“…Although previous studies have reported that the C‐terminal half of the protein (β9‐C‐terminus) exhibits lower stability than the N‐terminal half, our understanding of how the central β‐sheet and C‐terminal domain are disordered remains limited. In this study, we further characterized the pressure‐ and temperature‐stabilized intermediates of OspA using a paramagnetic relaxation enhancement (PRE)‐assisted NMR 23‐27 . The PRE effect arises from dipole‐dipole interactions between unpaired electrons of the paramagnetic agent and the nucleus of interest, and thus, spin relaxation contributions show r −6 dependence of distance between the paramagnetic center and nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Error (Δ R ) was defined using the sum of each Error at two time points t and 3 min as follows: where each Error ( R t ) was estimated from the signal/noise ratio (SNR) considering error propagation according to ( 53 ): …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, since PRE observation under high pressure is only limited in ubiquitin, the present is a confirmation of PRE under high pressure. 24 A combination of PRE-assisted high-pressure NMR and MD simulation is, in general, useful for characterizing the dynamic structures of functionally essential protein intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we further characterized the pressure-and temperature-stabilized intermediates of OspA using a paramagnetic relaxation enhancement (PRE)-assisted NMR. [20][21][22][23][24] The PRE effect arises from dipole-dipole interactions between unpaired electrons of the paramagnetic agent and the nucleus of interest, and thus, spin relaxation contributions show r -6 dependence of distance between the paramagnetic center and nucleus. Accordingly, when the paramagnetic agent was conjugated to a portion of the central domain, we were able to collect information on the distance between the central β-sheet and the N-and C-terminal domains.…”
Section: Introductionmentioning
confidence: 99%